Development of Low Cost Mobile Robot for Engineering and Technology Education - Abdul Hamid, Adom, PM Dr. (School of Mechatronic Engineering, 2008)
Ekspo ini berlangsung di Dewan Sek. Men. Putra, Kangar, Perlis.